2014
DOI: 10.1111/cen.12422
|View full text |Cite
|
Sign up to set email alerts
|

Cardio‐metabolic consequences of glucocorticoid replacement: relevance of ultradian signalling

Abstract: Summary Chronic exposure to elevated glucocorticoid levels is associated with obesity, insulin resistance, impaired glucose tolerance, hypertension and dyslipidaemia, manifest classically in Cushing's syndrome and with high‐dose glucocorticoid therapy. However, cardiovascular events are also reportedly higher in patients with primary and secondary hypoadrenalism receiving ‘replacement’ glucocorticoid doses. This has been attributed to an inability to mimic accurately the diurnal rhythm of cortisol with current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 80 publications
(161 reference statements)
2
9
0
Order By: Relevance
“…Indeed, the pattern of glucocorticoid exposure – and even the phase of the pulse – results in differential effects on behaviour and the c‐fos response of the brain – particularly the amygdala – to a stressor. This is also likely to lead to metabolic and cardiovascular dysfunction . Current replacement regimes with their relatively constant glucocorticoid receptor occupancy and consequent abnormal glucocorticoid‐dependent gene transcription undoubtedly contribute to glucocorticoid side effects and may even be a causal factor for the excessive morbidity and mortality of patients on glucocorticoid replacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the pattern of glucocorticoid exposure – and even the phase of the pulse – results in differential effects on behaviour and the c‐fos response of the brain – particularly the amygdala – to a stressor. This is also likely to lead to metabolic and cardiovascular dysfunction . Current replacement regimes with their relatively constant glucocorticoid receptor occupancy and consequent abnormal glucocorticoid‐dependent gene transcription undoubtedly contribute to glucocorticoid side effects and may even be a causal factor for the excessive morbidity and mortality of patients on glucocorticoid replacement.…”
Section: Discussionmentioning
confidence: 99%
“…This is also likely to lead to metabolic and cardiovascular dysfunction. [21][22][23] Current replacement regimes with their relatively constant glucocorticoid receptor occupancy and consequent abnormal glucocorticoid-dependent gene transcription undoubtedly contribute to glucocorticoid side effects and may even be a causal factor for the excessive morbidity and mortality of patients on glucocorticoid replacement. The current report shows that it is possible to reproduce near physiological patterns of both circadian and ultradian rhythmicity using a specialized pump and simple subcutaneous infusion techniques.…”
Section: Discussionmentioning
confidence: 99%
“…More subtly, clamping corticosterone in the mid-physiological range ablates the normal diurnal rhythmicity, activates NCC and induces non-dipping BP in mice ( Ivy et al, 2016 ). Interestingly, adrenalectomy also induces non-dipping BP in mice ( Sei et al, 2008 ) and in humans such circadian abnormalities have a detrimental impact on cardiovascular health ( Henley and Lightman, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of neural SAM-and HPA-mediated stress responses increases the release of epinephrine and corticosterone/cortisol, respectively, from adrenal glands, which in turn, produces tissue-specific homeostatic changes in metabolic and immune processes associated with the fight-or-flight response (Gorman, 2013). Chronic elevations of stress hormones have been associated with neurological abnormalities including psychosocial disorders and systemic inflammatory conditions (Barr, 2017;Henley and Lightman, 2014). We have previously shown that acute ozone-and acrolein-induced respiratory injury and inflammation are associated with the activation of neuroendocrine stress pathways in both healthy and diabetic rat models (Bass et al, 2013;Miller et al, 2015;Snow et al, 2017) and in healthy humans (Miller et al, 2016a).…”
mentioning
confidence: 99%